The Risk of Falling in Elderly Increased with Age Growth and Unaffected by Gender - Susilo, Wilson; Limyati, Yenni; Gunawan, Decky (Journal of Medicine and Health, 2017)
Elderly people are a group of people with age of 60 and above. Studies in United States showed one-third of elderly people experienced fall in their houses and one-forty of them need bedrest in hospital. Falling can cause physical and mental injury. Physical injury manifests as fracture, hematoma, bruises, and dislocation, and mental injury manifests as lack of self esteem. This study aimed to examine the relation between age and gender on risk of fall on elderly people. This is a cross-sectional analytical study involving 23 elderly people from Tulus Kasih Elderly Home that met the inclusion criteria. Risk of fall were checked with Timed Up and Go Test. The data acquired were analyzed with chi-square with Î± = 0,05. As results, age significantly affected risk of fall (p=0.019) but gender did not (p=0.265). We concluded the risk of falling is increased with age and unaffected by gender.Keywords : age, gender, risk of fall, timed up and go test